Prevalence and Correlates of Motoric Cognitive Risk Syndrome in Chinese Community-Dwelling Older Adults - Bai, Anying; Xu, Weihao; Lin, Zhanyi (Frontiers in Aging, 2022)
Background Motoric cognitive risk (MCR) syndrome is considered to be a pre-dementia syndrome. Although an increasing number of studies have begun to focus on this syndrome, few investigations have been launched in China. This study was performed to examine the prevalence and correlates of MCR in China. Methods We included 5725 adults aged over 60 years from China Health and Retirement Longitudinal Study (CHARLS). MCR was defined as the presence of subjective cognitive complaints and a gait speed ≤ 20th percentile of the weighted population distribution adjusted for sex and height. The associations among selected modifiable associated factors and clinical measures with MCR were examined using multivariate logistic regression analysis. Results Of the participants, 414 met the criteria for MCR with an overall prevalence 7.29% (95% CI: 6.62–7.96%). MCR was found to be more prevalent among women than men (9.73% vs. 4.85%), and more prevalent among participants ≥ 75 years than those < 75 years (7.85% vs. 5.23%). After multivariable adjustment, lower or upper extremity functional limitations, activities of daily living (ADL) disabilities, weak grip strength, exhaustion, and history of hypertension were found to be significantly associated with MCR. The multivariate analysis also showed higher levels of cystatin C and C-reactive protein were associated with increased odds for MCR. Conclusions The present study showed that MCR syndrome is highly prevalent among Chinese community-dwelling older adults, and revealed several factors that were correlated with MCR. Longitudinal studies are warranted to further explore the modifiable risk factors of MCR.